Optimized production and purification of Coxsackievirus B1 vaccine and its preclinical evaluation in a mouse model. Issue 30 (27th June 2017) - Hankaniemi, Minna M.; Laitinen, Olli H.; Stone, Virginia M.; Sioofy-Khojine, Amirbabak; Määttä, Juha A.E.; Larsson, Pär G.; Marjomäki, Varpu; Hyöty, Heikki; Flodström-Tullberg, Malin; Hytönen, Vesa P.
Highlights: An efficient CVB1 vaccine production and purification process was developed. Formalin inactivation caused a dramatic change in CVB1 integrity. Tween80 detergent increased CVB1 yield and stability significantly. CVB1 vaccine was immunogenic and protected mice against CVB1 infection. Abstract: Coxsackie B viruses are among the most common enteroviruses, causing a wide range of diseases. Recent studies have also suggested that they may contribute to the development of type 1 diabetes. Vaccination would provide an effective way to prevent CVB infections, and the objective of this study was to develop an efficient vaccine production protocol for the generation of novel CVB vaccines. Various steps in the production of a formalin-inactivated Coxsackievirus B1 (CVB1) vaccine were optimized including the Multiplicity Of Infection (MOI) used for virus amplification, virus cultivation time, type of cell growth medium, virus purification method and formulation of the purified virus. Safety and immunogenicity of the formalin inactivated CVB1 vaccine was characterized in a mouse model. Two of the developed methods were found to be optimal for virus purification: the first employed PEG-precipitation followed by gelatin-chromatography and sucrose cushion pelleting (three-step protocol), yielding 19-fold increase in virus concentration (0.06 µg/cm 2 ) as compared to gold standard method. The second method utilized tandem sucrose pelleting without a PEG precipitation step, yielding 83-fold increase in virus concentration (0.24 µg/cm 2 ), but it was more labor-intensive and cannot be efficiently scaled up. Both protocols provide radically higher virus yields compared with traditional virus purification protocols involving PEG-precipitation and sucrose gradient ultracentrifugation. Formalin inactivation of CVB1 produced a vaccine that induced a strong, virus-neutralizing antibody response in vaccinated mice, which protected against challenge with CVB1 virus. Altogether, these results provide valuable information for the development of new enterovirus vaccines.